E-BANKING IMPLEMENTATION AND TECHNOLOGY ACCEPTANCE IN THE RAFIDAIN AND RASHEED BANKS IN IRAQ: AN EMPLOYEE PERSPECTIVE - Riyadh, Hosam Alden; Sukoharsono, Eko Ganis; Baridwan, Zaki (The International Journal of Accounting and Business Society, 2015)
In the third millennium, e-banking system has been ad- opted globally in the banking industry. On the other hand, Iraq as a nation with less developed IT adoption has not integrated this system in its banking services, instead of its current acknowledgement on the advantages of e-banking technology in competition among banking service provid- ers. In contrast, Iraqi banks still keep on adopting tradi- tional banking system to deliver the majority of their ser- vices which in this case are paper-based work system. This is greatly resulted from the hesitation of bank employees to adopt new banking technologies. This study aims to identi- fy the impact of hypothesis between e-banking system and Iraqi banks employee perspective. This study was conduct- ed by taking sample of employee from two biggest public banks in Iraq which are AL-RAFIDAIN and AL-RASHEED. A survey through questionnaires on the website was used as the instrument to collect the data were analyzed us- ing PLS software. Technology Acceptance model(TAM) as a basic foundation with independent variables Perceived Usefulness, Perceived Ease of Use, Perceived IT Beliefs and Task–Technology Fit, Attitude as Intervening and Inten- tion to Use as dependent variable. The result of hypothesis analysis reveals that there is a significant impact among all variables to attitude, but Perceived Ease of Use, it does not apply variable from those analysis it is depicted that Perceived Ease of Use does not impact to the perception of the implementation of e-banking system in Iraqi banks. Keywords:E-banking System, Acceptance Theory model (TAM), Perceived IT Beliefs, Task–Technology Fit, Attitude, and Intention to Use.